Failure of WTO ministerial highlights systemic issues - Rogerson, Evan (2024)
The 13th Ministerial Conference of the World Trade Organization concluded without any significant multilateral results. At a time when economic nationalism is on the rise and multilateralism is under siege, failure to make progress at Abu Dhabi risks further weakening the WTO as an element of stability and conciliation. It leaves WTO members and senior management with serious questions to answer about the direction and effectiveness of the multilateral trading system.